The Shura Concept of Government in the View of Islam and Democracy - Yakin, Nur'l; Victoria, Ong Argo (Universitas Islam Sultan Agung, 2022)
This paper aims to briefly describe shura and will culminate in explaining the differences between shura and democracy which are products of secularism. This study uses a juridical theoretical approach by analyzing various kinds of literature, both Islamic literature and other documents about the concept of Majlis Shura and Democracy. The primary materials are in the form of Al-Qur'an and Sunnah Studies and the book Asy Shura fi al-Kitab wa as-Sunnah wa 'inda Ulama al-Muslimin by Prof. Dr. Muhammad bin Ahmad bin Salih ash-Salih. Then analyzed by reducing the data then concluded. The results of this study explain the basic concept of Shura in Islam, the urgency of the concept of Shura and the conditions for becoming a member of Shura and the similarities and differences between the concept of sura and democracy. The conclusion of this study is that shura and democracy are not the same, because shura is a method that originates from Rabb al-Basyar (Rabb of mankind), namely Allah, while democracy is the fruit of thought from weak humans which of course cannot be separated from deficiencies.